EFFECTS OF Paenibacillus polymyxa ON THE ASSOCIATION OF Rhizobium japonicum IN SOYBEAN ROOTS - Yustiano, Anton (Agros Journal of Agriculture Science, 2018)
Soybean plants can bind nitrogen (N2) in atmosphere through activity of nitrogen-fixing by bacteria Rhizobium japonicum, that formed in soybean roots in form of nodules or root nodules. Root nodules can generally bind nitrogen from air at 10 up to 12 DAP, depending on environmental conditions, soil, and temperature. Antagonist agent of Paenibacillus polymixa can affect the association of R. japonicum bacteria in rooting of soybean plants. Aim of this research is to know effect of P. polymixa to bacterial association of R. japonicum on rooting of soybean plants. Experiment was conducted at Pest Forecasting Institute Jatisari, Karawangin dry season of 2016. Experimental design was arranged in completely randomized design with six replications. Treatment consists of: 1) Soaking of soybean seeds with P. polymixa concentration 5 cc per l for 5 seconds; 2) Spraying of P. polymixa to soybean plant with a concentration of 5 cc per l of 3 cc at intervals of 10, 35, and 60 DAP; 3) Soaking of soybean seeds with P. polymixa concentration 5 cc per l for 5 seconds and spraying P. polymixa to soybean plant with concentration of 5 cc per l as much as 3 cc at interval 10, 35 and 60 DAP; and 4) Controls. Results showed that P. polymixa did not affect the association of R. japonicum bacteria in rooting of soybean plants that functioned in the formation of root nodules.